GAMBARAN HISTOPATOLOGI Clarias gariepinus YANG TERINFEKSI Edwardsiella tarda DI KEDIRI - JAWA TIMUR - Budi Rianto Wahidi; Novia Christi Prihartini (Jurnal Akuakultur Rawa Indonesia, 2022)
Clarias gariepinus is one of the freshwater fish that is easy to culture, but is also susceptible to Edwardsiella tarda infection. Although this is convenient to treated, the consequences of this bacterial infection are quite detrimental. The method used in this study is a biochemical test followed by histopathological examination to observe tissue changes that occur in the Clarias gariepinus organ. The results showed that 5 out of 17 samples were infected with Edwardsiella tarda with pathological features showing edema, congestion, lymphocyte infiltration, macrophage proliferation, and necrosis in all organs.